THE APPLICATION OF THE AMTSILATI METHOD IN IMPROVING THE ABILITY OF TRANSLATION OF THE YELLOW BOOK IN CLASS VII STUDENTS AT MADRASAH MU'ALLIMIN ADDINYAH AL HIKMAH 1 BENDA SIRAMPOG BREBES - Aminudin Aminudin (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
Abstrak The ability of students in translating the yellow book of love is low, and lack of understanding in how to translate the yellow book properly and correctly, so that it is easy to read and understand, because the method used previously was the confessional method which was passive and less effective for students. So it is necessary to apply an alternative method, namely the active Amtsilati method. The Amtsilati method is a fast method of understanding, reading, memorizing or interpreting, and translating the yellow book.This study aims to find out how to plan, implement and improve the ability to translate the yellow book in seventh grade students after the implementation of the Amtsilati method at Madrasah Mu'allimin Addiniyah Al-hikmah 1 Benda Sirampog Brebes? This study uses a qualitative approach, with a qualitative descriptive type and analysis. Data collection techniques by conducting interviews, observations, and documentation. Keywords: Application of Amtsilati Method, Translating Ability, Yellow Book.